The Effect of Earnings Management to Stock Liquidity in Manufacturing Companies Year 2009-2013 - Akami Pratama, Rommy Harisma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of establishing the company is to maximize the value of the company or increasing the prosperity of stockholders. This objective can be achieved if the company is able to operate properly so that it will appreciate the company’s stock price. It shows that there is relationship between company performances and company’s outstanding shares in the capital market. One of the company’s normative goals is to maximize the company’s value through the increase in stock prices. This may encourage managers to perform creative accounting through earnings management. The purpose of this research is to determine the effect of earnings management and stock liquidity in manufacturing companies in Indonesia Stock Exchange year 2009-2013. Research method used in this research is panel data regression using software EViews 6. This research uses the dependent variable stock liquidity, while the independent variable is the earnings management. Results from this research indicate that there is a relationship between earnings management and stock liquidity but it did not show any significant effect. This supports the assumption that says that the practice of earnings management indicates poor company performance. Research on the upcoming future, needs to be studied more in depth about the stock liquidity by using other factors to maximize the results of research. Keywords: Earnings Management, Stock Liquidity, Accounting Theory, Companies